Bariatric surgery: impact on sexuality of the obese person - Mariano,Maria Luiza Lobato (2014)
Objective: To assess the impact of surgical treatment in the sexuality of the obese.Methods: We conducted a qualitative / quantitative research with 30 patients who had undergone Fobi-Capella Roux-Y gastric bypass for at least one year. We collected data through individual interviews using a questionnaire with 10 mixed questions and one open, between May and June 2011. The objective data were quantified in absolute numbers and percentages, and the subjective ones were analyzed using the Discourse of the Collective Subject (DCS) and discussed in view of reference published on the subject.Results: 30 patients were enrolled, with a mean age 44 ± 12 years, 24 (80%) were female and six (20%) were male, 23 (77%) were married, 23 (96%) were hypertensive and eight (33%) were diagnosed with Diabetes Mellitus. After the operation, 11 (37%) individuals reported no change in the number sexual intercourses, but 19 (63%) reported that this number was altered, 16 (53%) informed increased frequency, one (3%) reported a decrease in frequency, one (3%) did not practice sexual intercourse anymore and one (3%) did not report the frequency. The central ideas (CI) raised originated four DCSs: Experience of female sexuality; No experience of female sexuality; Experience of male sexuality; and improvements of comorbidities and psychological factor.Conclusion: there are positive repercussions of physical and emotional orders of the surgical treatment of obesity, favoring the quality of life, including sexuality.